Evaluation of Impressed Potential on Buried Pipelines Near HVDC Grounding Electrodes Considering the Polarization Effect - Bo Zhang; Fangyuan Cao; Xiaobo Meng (CSEE Journal of Power and Energy Systems)
When a long distance HVDC transmission system discharges current into the earth through its grounding electrode, ground potential differences appear in a large area. And therefore part of the DC current may flow into nearby pipelines which may be dangerous to the equipment and personnel, and may aggravate corrosion. In this paper, an equivalent circuit based on the method of moments is introduced to calculate the current and potential distributions along a pipeline with damaged anticorrosive coating. The current-dependent electrochemical polarization potential between soil and the metal pipe, due to the damage of the anticorrosive coating, is taken into account by using the Newton-Raphson scheme. The circuit is verified through a reduced scale experiment. By examining the circuit, the effect of the damaged anticorrosive coating on the leakage current and the pipe potential with respect to soil along the pipeline is analyzed.